Design and Develop A Secure Energy Efficient Data Transmission Technique for Wireless Sensor Networks - Avneesh Gour, Nishant Kumar Pathak (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Wireless Sensor Networks (WSNs) play a vital role in various applications such as environmental monitoring, healthcare, and smart cities. However, energy consumption is a critical concern in WSNs due to the limited power supply of sensor nodes. This research paper proposes a novel approach to address this challenge by designing and developing a secure energy-efficient data transmission technique for WSNs. The proposed technique aims to minimize energy consumption while ensuring data confidentiality, integrity, and authenticity. By leveraging cryptographic algorithms, optimization strategies, and intelligent routing protocols, the proposed technique enhances the security and efficiency of data transmission in WSNs. Experimental results demonstrate the effectiveness and feasibility of the proposed approach in improving the overall performance of WSNs in terms of energy consumption, communication overhead, and security.